Vertical jump performance after passive static stretching of knee flexors muscles - Mendes Leal de Souza, L.; Andrade Paz, G.; Eloi, I. L.; Dias, R.; de Freitas Maia, M.; Miranda, H.; Pinheiro Lima, V. (Apunts Medicina de l'Esport, 2016)
The purpose of this study was to investigate the acute effects of passive static stretching (PSS) applied on hamstring muscles on vertical jump height (VJ) performance. Materials and methods: Ten men and 10 women with previous experience in resistance training were volunteers, and performed two protocols on non-consecutive days: traditional protocol (TRAD) including VJ without previous PSS, and a PSS protocol, with VJ immediately after stretching. Results: Significant differences were observed in VJ performance with PSS (53.6 ± 8.5 cm) when compared to TRAD (47.9 ± 13.1 cm) for the women's group (p = 0.021). Significant differences were also observed in the men's group with PSS (58.4 ± 12.3) versus TRAD (51.4 ± 9.6) protocol (p = 0.001). Conclusion: These results suggest that PSS applied only on hamstring muscles may have an acute effect on increasing the VJ performance for both men and women with previous experience in resistance training.